Carbon Dioxide Laser for the Treatment of Microcystic Lymphatic Malformations (Lymphangioma Circumscriptum): A Systematic Review. Issue 8 (22nd April 2013) - Savas, Jessica A.; Ledon, Jennifer; Franca, Katlein; Chacon, Anna; Zaiac, Martin; Nouri, Keyvan
<x xml:space="preserve">Abstract</x> Background Lymphangioma circumscriptum (LC) is a rare, superficial, cutaneous lymphatic malformation. Management is difficult because of high recurrence rates, regardless of the treatment modality chosen. The carbon dioxide (CO2) laser may offer a less‐invasive option than surgery that provides satisfactory functional and cosmetic results. Objectives To systematically review the efficacy and safety of the CO2 laser for the treatment of LC. Methods The terms "lymphangioma circumscriptum" and "microcystic lymphatic malformation" were combined with "treatment, " "laser, " and "carbon dioxide" during separate searches in the PubMed database. The articles retrieved were then evaluated based on set criteria. Results We identified 16 studies (11 case reports, 5 case series) with a total of 28 separate patients who had been treated for LC using a CO2 laser. Eight patients remained disease free from 4 months to 3 years, 10 experienced partial recurrence, and two experienced complete recurrence. Various laser parameters were reported, and adverse effects were generally minor and infrequent, such as dyspigmentation and mild scarring. Conclusions Available evidence indicates that the CO2 laser is a safe and efficacious option for the treatment of LC, particularly in large lesions that may not be amenable to surgical intervention.